2010
DOI: 10.1016/j.jacc.2010.03.090
|View full text |Cite
|
Sign up to set email alerts
|

Testosterone Therapy in Women With Chronic Heart Failure

Abstract: Testosterone supplementation improves functional capacity, insulin resistance, and muscle strength in women with advanced CHF. Testosterone seems to be an effective and safe therapy for elderly women with CHF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
67
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 183 publications
(70 citation statements)
references
References 38 publications
1
67
0
2
Order By: Relevance
“…39 Therefore, androgen deficiency may be involved in the imbalance between anabolic and catabolic processes and contribute to heart failure-induced muscle wasting and cachexia. 65 Testosterone supplementation was evaluated in small randomized double-blind studies including elderly men 66 and women 67 with heart failure. As testosterone improved functional capacity and muscle strength, it was hypothesized that it could be safe and useful in heart failure and cardiac cachexia.…”
Section: Cachexia Prevention and Treatmentmentioning
confidence: 99%
“…39 Therefore, androgen deficiency may be involved in the imbalance between anabolic and catabolic processes and contribute to heart failure-induced muscle wasting and cachexia. 65 Testosterone supplementation was evaluated in small randomized double-blind studies including elderly men 66 and women 67 with heart failure. As testosterone improved functional capacity and muscle strength, it was hypothesized that it could be safe and useful in heart failure and cardiac cachexia.…”
Section: Cachexia Prevention and Treatmentmentioning
confidence: 99%
“…140143 Toma et al performed a meta‐analysis of these studies and discovered that there was a net pooled improvement of 0.52 standard deviations in exercise capacity among those who were treated with testosterone. 144 The meta‐analysis revealed that patients treated with testosterone replacement therapy experienced an increase of 16.7% (equivalent to ≈54 m) in the 6‐minute walk test, an increase of 15.9% in the isometric walk test, and finally an increase of 22.7% in peak VO 2 .…”
Section: Testosterone and Congestive Heart Failurementioning
confidence: 99%
“…However, peak oxygen uptake, Beck Depression Inventory, leg strength, and several quality of life components were more improved in former interventional group [27]. Similarly, Iellamo et al showed that 6MWD, peak oxygen consumption, maximal voluntary contraction, and peak torque increased significantly in testosterone group but remained unchanged in control group [28]. In a recent meta-analysis, a significant increase was shown in exercise capacity following testosterone therapy [29].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, association between the lack of testosterone and stimulating inflammatory responses has been shown and thus a remarkable improvement of cardiac performance and a significant decrease in the level of serum TNF-alpha following testosterone therapy has been suggested [33]. Along with the pointed mechanisms, a rise in hemoglobin [34], improvement of baroreceptor sensitivity [35], increase of muscle sympathetic nerve activity, and an increase of muscle arteriole vasodilation and function [36] have been also proposed. In addition, because insulin resistance is a major metabolic disturbance occurring in up to 40% of heart failure patients [37], this abnormality has been shown to be associated with low testosterone level leading decreased glucose utilization by skeletal muscle that results in muscle fatigue and wasting [38, 39].…”
Section: Discussionmentioning
confidence: 99%